The impact of differences planting date against morphological characters of some wheat genotype in Berastagi of Karo District - Dafni Mawar Tarigan; . Rosmayati; Chairani Hanum; Lollie A.P. Putri (Syiah Kuala University, 2013)
Optimal planting date is one of the important factors affecting the wheat crop. Improper planting date can lead to a drastic decrease in wheat yield. Therefore, information about the adaptation of wheat plants at planting date at a particular location will benefit farmers in determining how best to utilize the wheat plants in each production system through morphological characters. Then conducted research The Impact of Differences Planting date against Morphology Character of some Wheat Genotypes in Berastagi of Karo district to determine the most appropriate wheat genotypes grown in Berastagi at certain times growing season through morphological characters. This research was conducted at Berastagi with two planting date (planting date I = late February to early June 2012 and planting date II = late October 2012 to early February 2013), using a Randomized Block Design (RBD) non factorial using 12 wheat plant,namely 2 varieties (Selayar / K and Dewata / L) and 10 genotypes that OASIS / SKAUZ / / 4 * BCN (A); HP1744 (B); LAJ3302 / 2 * MO88 (C); RABE / 2 * MO88 (D), H-21 (E), G-21 (F), G-18 (G); MENEMEN (H); BASRIBEY (I); ALIBEY (J). Observational data were tested with analysis of variance and combined analysis.The observed morphological characters were plant height, number of spikelet spike-1, number of grainspike-1 and grain weight spike-1. The results of analysis of variance and combined analysis showed that all parameters were observed give significantly different results for each planting date.